Improved enzymatic two-phase biotransformation for (R)-phenylacetylcarbinol: Effect of dipropylene glycol and modes of pH control - Leksawasdi N. (2014)
An octanol/aqueous two-phase process for the enzymatic production of (R)-phenylacetylcarbinol (PAC) has been investigated further with regard to optimal pH control and replacement of 2.5 M MOPS buffer by a low cost solute. The specific rate of PAC production in the 2.5 M MOPS system controlled at pH 7 was 0.60 mg U-1 h-1 (reaction completed at 34 h), a 1.6 times improvement over the same 2.5 M MOPS system without pH control (0.39 mg U-1 h-1 at 49 h). An improved stability of PDC was evident at the end of biotransformation for the pH-controlled system with 84% residual carboligase activity, while 23% of enzyme activity remained in the absence of pH control. Lowering the MOPS concentration to 20 mM resulted in a lower benzaldehyde concentration in the aqueous phase with a major increase in the formation of by-product acetoin and three times decreased PAC production (0.21 mg U-1 h-1). Biotransformation with 20 mM MOPS and 2.5 M DPG as inexpensive replacement of high MOPS concentrations provided similar aqueous phase benzaldehyde concentrations compared to 2.5 M MOPS and resulted in a comparable PAC concentration (92.1 g L-1 in the total reaction volume in 47 h) with modest formation of acetoin. © 2005 Taylor & Francis.